Questions to tourists stopped by Walden pond: Waterscapes, words and literary tourism - Fernandes Alves, Isabel Maria (LIT&TOUR – International Journal of Literature and Tourism Research (IJLTR), 2023)
The purpose of this paper is twofold: first, to analyze the meaning of Walden Pond, a real body of water between Concord and Lincoln, Massachusetts, as it appears in Henry David Thoreau’s Walden (1854). This pond is first and foremost a place on whose shores the writer decided to live between 1845 and 1847. Secondly, the literary representation of the lake functions as a symbol of simplicity, of observation and knowledge, and, in this sense, I seek to investigate how Thoreau’s words about the Walden pond have contributed to the (trans)formation of readers’ and tourists’ minds. Moreover, my interest is to draw from works about literary tourism and to see how literary words construct the tourist vision, as “in literary tourism, narratives act as the primary source of information about a place, stimulating motivation to travel” (Charapan & Mikulich, 2019). Thus, my proposal aims to show that because water is characterized as mirrorlike, windowlike, and with no definite shape it is a fertile metaphor for poetic imagery. Additionally, to evince that (literary) words, place, waterscapes and tourists interrelate in the forging of (new) consciousnesses, better suited to practice reverence for our common home.